The Principles of Biology, Volume 2 (of 2) - Spencer, Herbert, 1820-1903 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Principles of Biology, Volume 2 (of 2)" by Herbert Spencer is a scientific publication written in the late 19th century. This work delves into biological concepts, focusing on the principles of morphology and physiology in living organisms. Spencer aims to analyze and explain the evolutionary processes that shape both plants and animals, providing a comprehensive view of the interrelation between structure and function in the organic world. The opening of the second volume includes a preface outlining revisions and expansions made to the original text, emphasizing that while some updates are new, the foundational ideas mostly remain unchanged from earlier editions. Spencer acknowledges contributions from various scholars in reviewing anatomical and functional aspects of organisms. He sets the stage for discussing morphological development, illustrating the complexities of organism composition and the interaction between structures and their functions, laying the groundwork for a discussion that remains rooted in the principles of evolution. The chapter begins by presenting the problems and methodologies involved in understanding morphology, thereby hinting at a detailed exploration of both plant and animal structures in subsequent sections. (This is an automatically generated summary.)
Release date is 2022-01-30
Karin Spence, Tim Lindell, Adrian Mastronardi, Josep Cols Canals and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Biology